[en] URBAN DYNAMICS AND MECHANISMS OF GENTRIFICATION IN THE FAVELAS OF RIO DE JANEIRO ON THE EVE OF MEGA-EVENTS: THE CASE OF THE FAVELA CHAPÉU MANGUEIRA - CLARA MONA LISA BOVIER (MAXWELL, 2018)
[pt] O Rio de Janeiro vivencia uma época intensa da sua história urbana, hospedando diferentes megaeventos em um intervalo de tempo limitado, dando origem a uma fase de metamorfoses urbanas e de alta especulação imobiliária. Neste contexto a presente dissertação se propõe a observar a problemática da condição das favelas contíguas aos bairros nobres da cidade e da valorização dos seus solos. O objetivo dessa pesquisa é identificar as dinâmicas políticas, econômicas e sociais existindo hoje em dia no Rio de Janeiro, intrometendo-se no desenvolvimento urbano, e podendo levar a uma gentrificação das favelas no coração da cidade, em particular no caso de estudo do Chapéu Mangueira. O trabalho baseou-se numa revisão bibliográfica sobre o conceito de gentrificação, tanto no contexto internacional quanto brasileiro, em análises do contexto político, econômico e social da cidade e das ações de planejamento urbano, bem como no estudo de caso de uma favela: Chapéu Mangueira, localizada no Leme, na Zona Sul da cidade do Rio de Janeiro. === [en] The city of Rio de Janeiro is experiencing an intense time of its urban history, hosting different mega events in a short period of time, giving rise to a phase of urban metamorphoses and high real estate speculation. In this context, the present work aims to observe the problem of the condition of the favelas adjacent to wealthy neighborhoods of the city and its land valuation. In fact, the Carioca capital, on one hand, still attracts more residents, investors and entrepreneurs and, on the other hand, its most valued central areas are already overcrowded and do not have much options to grow. Urban expansion possibilities exist, but are located in remote areas and have neither infrastructure nor sufficiently attractive centrality to raise interest of certain kind of residents. Because of a limited housing supply and a high demand, rental prices and sales increase steadily. Consequently, the rise in housing value hinders public access opportunities, especially as wage inflation does not track the value of the property. Like many cities in Latin America, the social inequalities in Rio de Janeiro are extremely important and a significant part of the population is classified as low income. At the same time, one of its peculiarities is the presence of favelas in the city center, unlike other cities where the poorest people are located in the urban periphery. The particular feature of the promiscuity of the hills with the noble neighborhoods and trade areas and service of the city makes these favelas strategic areas, with crucial importance in the distribution of urban land. The lack of sanitation and basic infrastructure combined with drug trafficking and violence always left the favelas apart of the formal city. The government did not recognize their existence as part of the city. Today, with urban growth contained and the pressure of international events becoming stronger, the government has shown new interest in the future of this part of the town. Different actions, such as the implementation of the UPPs (Pacifying Police Unit) and works to facilitate access to the favelas, tend to value the land and drawing attention of the real estate market. Materials and studies on the fever of chic favela, new tourist and cultural attraction to these neighborhoods, have also questioned a change of perception of the favela. It has already been observed a rise in rental and sale prices, whether in formal or informal market in the favela.